Effect of the Polyamine-Spermine on Agonist-Induced Human Platelet Activation - Specific Inhibition of "Aggregation-Independent" Events Induced by Thrombin, but not by Collagen, Thromboxane Mimetic, Phorbol Ester or Calcium lonophore - Joseph, Sunil; Krishnamurthi, Sushila; Kakkar, Vijay V (Thrombosis and Haemostasis, 1987)
Spermine, a naturally occurring polyamine, has previously been described as an inhibitor of purified phospholipase C and protein kinase C in cell-free systems. The present study examines the effect of spermine on platelet aggregation, dense-granule secretion and thromboxane (Tx) B2 synthesis induced by a variety of agonists, which cause the activation of one or both enzymes to different extents. These studies revealed that, while spermine (10 mM) inhibited platelet aggregation in response to all the agonists examined, [14C]-5-hydroxytryptamine (5HT) release and TxB2 synthesis induced by thrombin (0.2 U/ml) and collagen (10-40 μg/ml) alone, were inhibited by spermine, the percentage inhibition being >90% for both responses with thrombin, 30% for 5HT release and 80% for TxB2 synthesis with collagen. The inhibition of collagen-induced [14C]-5HT secretion by spermine was due entirely to the inhibition of aggregation-dependent TxA2 synthesis as addition of a sub-threshold concentration of U46619, which induced no secretion on its own, totally restored collagen-induced [14C]-5HT secretion to the levels seen in the absence of spermine. Moreover, collagen-induced TxB2 formation in unstirred platelets, which occurred independently of aggregation was not significantly affected by spermine (10 mM). However, the inhibition of maximal thrombin-induced [14C]-5HT secretion and TxB2 synthesis, which are both aggregation-independent phenomena, could be attributed to the inhibition of thrombin-induced diacylglycerol formation and intracellular calcium mobilization, which were both inhibited by 80% in the presence of spermine. These results suggest that spermine may be a specific inhibitor of thrombin-induced platelet responses rather than a generally effective inhibitor of platelet phospholipase C and protein kinase C or the activation of these enzymes in response to agpnists other than thrombin, at least when added exogenously to intact platelets. This thrombin-specific inhibition may be due to an interference of the binding of thrombin to its platelet receptor and/or interference at a step following thrombin binding, which is involved in the subsequent coupling processes.
Keywords: Spermine; Platelets; Thrombin; Anti-platelet drug